2019
DOI: 10.1002/eji.201948357
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor binding at Ig enhancers is linked to somatic hypermutation targeting

Abstract: Secondary diversification of the Ig repertoire occurs through somatic hypermutation (SHM), gene conversion (GCV), and class switch recombination (CSR)—three processes that are initiated by activation‐induced cytidine deaminase (AID). AID targets Ig genes at orders of magnitude higher than the rest of the genome, but the basis for this specificity is poorly understood. We have previously demonstrated that enhancers and enhancer‐like sequences from Ig genes are capable of stimulating SHM of neighboring genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 103 publications
(175 reference statements)
0
11
0
Order By: Relevance
“…E2A/E2-2 DKO mice have impaired CSR to IgE, due to loss of activation of the 3’RR enhancer and IgE GLT ( 85 ). Further, E-box binding sites within Ig enhancers promote efficient SHM ( 96 99 ). E2A may help direct AID to DNA, and genome wide E2A occupancy is associated with AID targeting ( 99 ).…”
Section: Mature B Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…E2A/E2-2 DKO mice have impaired CSR to IgE, due to loss of activation of the 3’RR enhancer and IgE GLT ( 85 ). Further, E-box binding sites within Ig enhancers promote efficient SHM ( 96 99 ). E2A may help direct AID to DNA, and genome wide E2A occupancy is associated with AID targeting ( 99 ).…”
Section: Mature B Cell Developmentmentioning
confidence: 99%
“…Further, E-box binding sites within Ig enhancers promote efficient SHM ( 96 99 ). E2A may help direct AID to DNA, and genome wide E2A occupancy is associated with AID targeting ( 99 ). Finally, we suggest that E2A proteins act to promote CSR and SHM by initiating loop extrusion across the switch regions and V gene segments and note that E2A likely plays an additional role in promoting phase separated droplets to orchestrate CSR and SHM.…”
Section: Mature B Cell Developmentmentioning
confidence: 99%
“…This location also ensures that gene conversion in the B cell lineage will be focused on the light chain transgene. 40,41 The variable region is a pre-rearranged VK3-15/JK1 region made by joining the germline gene segments together, with no chewing back of the ends. This rearranged sequence is expressed in humans, as it is found in the National Center for Biotechnology Information's Expressed Sequence Tags database.…”
Section: Generation Of Omniclic Birdsmentioning
confidence: 99%
“…20). Comparisons were made by studying other EBV-immortalized B cell lines derived from 3 different healthy donors, an AID-deficient patient (AID -/-), and a uracil N-glycosylase-deficient (UNG-deficient) patient (UNG -/-), as well as unmodified CTNNBL1 M/M Ramos B cells and CRISPR/ Cas9-edited AID -/-Ramos B cells that lack AID expression ( Fig 23,24). We found that CTNNBL1 expression in both the patient EBV BLCLs and the CTNNBL1 466 V/V Ramos B cells was similar to expression in control EBV-derived BLCLs and Ramos B cells, showing that the M466V missense mutation does not appear to alter the CTNNBL1 cellular pool ( Figure 2).…”
Section: Disease-associated Ctnnbl1 Mutation Impairs Somatic Hypermutmentioning
confidence: 99%